Active Networks
DOI: 10.1007/978-3-540-71500-9_4
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Instrusion Prevention in Active and Extensible Networks

Abstract: Abstract. The proliferation of computer viruses and Internet worms has had a major impact on the Internet Community. Cleanup and control of malicious software (malware) has become a key problem for network administrators. Effective techniques are now needed to protect networks against outbreaks of malware. Wire-speed firewalls have been widely deployed to limit the flow of traffic from untrusted domains. But these devices weakness resides in a limited ability to protect networks from infected machines on other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Snapp et al [15] demonstrated a prototype of Distributed IDS (DIDS) that combines distributed monitoring and data reduction with centralized data analysis (through the DIDS Director). A Distributed Intrusion Prevention System (DIPS) has been proposed by Sproull et al [16]. Our work is complementary to these approaches focusing on the flexible use of network and cloud resources across different domains to realize security functions in a distributed setting.…”
Section: Related Workmentioning
confidence: 96%
See 1 more Smart Citation
“…Snapp et al [15] demonstrated a prototype of Distributed IDS (DIDS) that combines distributed monitoring and data reduction with centralized data analysis (through the DIDS Director). A Distributed Intrusion Prevention System (DIPS) has been proposed by Sproull et al [16]. Our work is complementary to these approaches focusing on the flexible use of network and cloud resources across different domains to realize security functions in a distributed setting.…”
Section: Related Workmentioning
confidence: 96%
“…(This remains true in practice despite various earlier efforts towards distributed intrusion detection systems [5,7,16].) Specifically, while security professionals at different organizations readily exchange intelligence through personal communication, there is no systematic way to follow a lead to a remote location to investigate the potential source of an attack.…”
Section: Introductionmentioning
confidence: 95%
“…DEIDtect [23] is an elastic distributed intrusion detection framework that decouples the location of the protected network from IDS/IPS in the cloud and enterprise network. [24] shows the cooperation of active network management software and extensible hardware to stop an attack.…”
Section: Related Workmentioning
confidence: 99%